CUDC‐907 blocks multiple pro‐survival signals and abrogates microenvironment protection in CLL. Issue 1 (24th October 2018) - Chen, Yixiang; Peubez, Chloé; Smith, Victoria; Xiong, Shiqiu; Kocsis‐Fodor, Gabriella; Kennedy, Ben; Wagner, Simon; Balotis, Constantine; Jayne, Sandrine; Dyer, Martin J. S.; Macip, Salvador
Abstract: CUDC‐907, a dual PI3K/HDAC inhibitor, has been proposed to have therapeutic potential in hematopoietic malignancies. However, the molecular mechanisms of its effects in chronic lymphocytic leukaemia (CLL) remain elusive. We show that CLL cells are sensitive to CUDC‐907, even under conditions similar to the protective microenvironment of proliferation centres. CUDC‐907 inhibited PI3K/AKT and HDAC activity, as expected, but also suppressed RAF/MEK/ERK and STAT3 signalling and reduced the expression of anti‐apoptotic BCL‐2 family proteins BCL‐2, BCL‐xL, and MCL‐1. Moreover, CUDC‐907 downregulated cytokines BAFF and APRIL and their receptors BAFFR, TACI, and BCMA, thus blocking BAFF‐induced NF‐κB signalling. T cell chemokines CCL3/4/17/22 and phosphorylation of CXCR4 were also reduced by CUDC‐907. These data indicated that CUDC‐907 abrogates different protective signals and suggested that it might sensitize CLL cells to other drugs. Indeed, combinations of low concentrations of CUDC‐907 with inhibitors of BCL2, BTK, or the NF‐κB pathway showed a potent synergistic effect. Our data indicate that, apart from its known functions, CUDC‐907 blocks multiple pro‐survival pathways to overcome microenvironment protection in CLL cells. This provides a rationale to evaluate the clinical relevance of CUDC‐907 in combination therapies with other targeted inhibitors.